Namibia : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that Namibia's real GDP growth accelerated to an estimated 4u percent in 2004, after averaging about 3 percent during the preceding five years. Growth benefited from declining interest rates, as the Bank of Namibia took advantage of declining inflation pressures and reduced its key policy rate in several steps from 12 3/4 percent in January 2003 to 7 1\2 percent in July 2004. Executive Directors have welcomed the recent rise in GDP growth, decline in inflation, and strengthening of the external current account surplus.